Pregnancy in patients affected by axial-spondyloarthritis: a narrative review of disease activity and obstetric outcomes - M. Filippini; G. Fontana; P. Bizioli; F. Crisafulli; R. Orabona; S. Zatti; F. Franceschini; A. Tincani (PAGEPress Publications, 2024)
Objective. This review aims to summarize the most recent and updated data on pregnancy in patients with axial spondyloarthritis (axSpA), focusing on the recurrence of pregnancy-related complications, the disease activity throughout gestation and the postpartum, and the latest indications for the treatments of future mothers. Methods. We have conducted a narrative review with an online literature search on Medline and PubMed. We selected only studies written in English published until January 2024, including observational and retrospective studies, meta-analyses, and systematic reviews. Results. Proper preconception counseling and maternal-fetal monitoring are necessary to ensure the best outcome for both the mother and her baby. Despite the limited and conflicting evidence about the prevalence of adverse pregnancy outcomes in women with axSpA compared to healthy controls, primary findings demonstrate an increased risk of preterm delivery (PTD), low birth weight (LBW), and elective cesarean section (CS). Concerning disease activity, data suggests that 25-80% of women with ankylosing spondylitis experience disease flares during pregnancy, particularly around 20 weeks of gestation. On the contrary, the data on the postpartum disease flare are heterogeneous. The use of biological drugs in pregnancy is safe and effective in controlling disease activity. Conclusions. Data on pregnancy outcomes in patients with axSpA are scarce and discordant. Probably the difference in maternal disease classification, the evolution of treatment indications, and the differences emerging from study designs can account for these discrepancies. The main evidence shows an increased risk of PTD, LBW, and elective CS (although the latter may reflect cultural influences rather than medical needs due to axSpA itself). The majority of drugs used to treat axSpA, including TNFi, are safe in pregnancy without harming mothers or fetuses. Further data is needed to clarify many controversial aspects in this area.